Parental Behaviors, Emotions at Bedtime, and Sleep Disturbances in Children with Cancer. (11th April 2020) - Kim, Hyun; Zhou, Eric S; Chevalier, Lydia; Lun, Phyllis; Davidson, Ryan D; Pariseau, Emily M; Long, Kristin A
Abstract: Background: Poor sleep is common for children during cancer treatment, but there is limited understanding of the nature of children's sleep throughout the treatment trajectory. The current exploratory study used an explanatory sequential mixed method approach to examine quantitative associations among sleep problems in children with cancer, parental behavior, and children's sleep hygiene, with follow-up qualitative characterizations of children's sleep across cancer treatment stages. Procedure: Eighty parents of children with cancer (aged 2–10 years; in active treatment, maintenance treatment, or off treatment) completed an online survey querying the child's sleep quality (Sleep Disturbance Scale for Children—Disorders of Initiating and Maintaining Sleep subscale) and behaviors (Child Sleep Hygiene Scale) and sleep-related parenting behaviors (Parental Sleep Strategies). A subsample ( n = 17 parents) participated in qualitative interviews to better characterize the processes of children's sleep and parents' sleep-related behaviors. Results: Children's sleep quality, sleep hygiene, or parental sleep strategies were not significantly different by cancer treatment groups. Greater sleep disturbance in children was associated with their parents' tendency to accommodate the child's bedtime requests. Qualitatively, cancer treatment-related anxiety in both children and parents influence the onset of these disruptive sleep behaviors. Conclusion: Parents' sleep-related behaviors affect children's sleep during cancer treatment. Parents' accommodation may start during active treatment to alleviate cancer-related challenges, and these behaviors may continue into maintenance therapy and off treatment to reinforce sleep disturbance. Behavioral interventions targeting unhelpful parental behaviors may improve sleep in children with cancer during and after cancer treatment.